Optimalisasi Deteksi Dini Penyakit Tidak Menular pada Wanita Usia Produktif Melalui Implementasi Program CANTIK SEHAT di Puskesmas Dungingi - Sri Andriani Ibrahim; Sitty Fadhilla Fitrianty Lahay; Astri Anita; Taufiq Qurrohman; ⁠⁠Nurfahira Salim; ⁠⁠Nur Mir’atul Ginaya Rahman; Ananda Syakbaniah Herman Rauf (Universitas Negeri Gorontalo, 2026)
The CANTIK SEHAT program at Dungingi Primary Health Center aims to facilitate early detection of Non-Communicable Diseases (NCDs) among women of reproductive age. This descriptive quantitative study with a cross-sectional approach involved 55 respondents in November 2025, utilizing clinical breast screening (USG), anthropometry, and hemodynamic-metabolic examinations. Results revealed that 7.27% of respondents were at high risk for breast tumors, with 31.48% showing USG abnormalities. Regarding metabolic risks, the prevalence of obesity reached 69.1%, pre-hypertension 56.4%, and moderate diabetes risk was 65.5%. Most cases were asymptomatic, highlighting an NCD